2013
DOI: 10.1111/all.12199
|View full text |Cite
|
Sign up to set email alerts
|

Macrolides for the long-term management of asthma - a meta-analysis of randomized clinical trials

Abstract: Macrolide administration for asthma for three or more weeks was not associated with improvement in FEV1, but produced significant improvements in peak expiratory flow, symptoms, quality of life, and airway hyper-reactivity. Macrolides may therefore be beneficial as adjunct asthma therapy. Future trials, focusing on long-term safety and effectiveness, should use standardized outcomes and procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 49 publications
(146 reference statements)
0
41
0
Order By: Relevance
“…Additionally, the results also found the prolonged macrolide antibiotics administration can improve the neutrophil and eosinophil cells count of sputum among Asian, but not in Caucasian. The following reasons may explained the different results when compared with Richeldi's [36] and Reiter's [37] studies: (1) More articles which came from different countries were included in our meta-analysis, and the present results might be more closer to the real values; (2) We corrected some statistics and data errors in the Reiter's meta-analysis, so our meta-analysis pooled results may reduced bias and errors; 3) To evaluate the ethnicity-specific effects, we performed a subgroup analysis by ethnicity group. The subgroup analysis results might indicated the macrolides have different functions with different ethnicities.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Additionally, the results also found the prolonged macrolide antibiotics administration can improve the neutrophil and eosinophil cells count of sputum among Asian, but not in Caucasian. The following reasons may explained the different results when compared with Richeldi's [36] and Reiter's [37] studies: (1) More articles which came from different countries were included in our meta-analysis, and the present results might be more closer to the real values; (2) We corrected some statistics and data errors in the Reiter's meta-analysis, so our meta-analysis pooled results may reduced bias and errors; 3) To evaluate the ethnicity-specific effects, we performed a subgroup analysis by ethnicity group. The subgroup analysis results might indicated the macrolides have different functions with different ethnicities.…”
Section: Discussionmentioning
confidence: 92%
“…Unfortunately, only small number of included studies, so there is insufficient power to support or oppose the use of macrolides in asthma patients. In 2013, Reiter et al also conducted a meta-analysis to assess the efficacy of macrolides for long-term management in patients with asthma [37]. In the study, the results indicated that prolonged macrolides used in the patients with asthma couldn't improve the FEV1, but it can improve the PEF, QOL, AHR and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of four randomised controlled trials identified improvement in symptoms, quality of life and airway hyper-reactivity, but highlighted the limited statistical power to detect significant differences in lung function (23) .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…In recent years, macrolide antibiotics have been explored in several clinical trials for their effects on patients with CLD, including COPD, asthma, cystic fibrosis (CF), and non CFbronchiectasis (3,(5)(6)(7)(8)(9)(10)(11)(12)(13). Recently, several meta-analyses collected the data and confirmed that the long-term use of macrolides improves the quality of life of CLD patients by improving lung function and decreasing the frequency of acute exacerbations (14,15). However, no study has focused on their detrimental effects, especially on microbiological aspects.…”
mentioning
confidence: 99%